Mauritanie 1956-1963 : les multiples dimensions d’une indépendance contestée - Camille Evrard (L’Année du Maghreb)
This article aims to describe the contingent and painstaking character of the decolonization process and the complex conditions in which the empowerment of postcolonial elites took place, by going back to the period framing the independence of Mauritania, proclaimed in November 1960. This contribution looks to improve our knowledge of the tense atmosphere that prevails in this country, target of several attacks between 1956 and 1963, and subject to an imposing military mobilization along its borders with the Spanish Sahara and Algeria at war. The colonial, then Mauritanian authorities, has developed a speech aimed at fighting the Moroccan claims on the territory, while monitoring the allegiances of the Saharan populations and centrifugal political movements. The multi-scale analysis shows how the specificities of the Mauritanian entity and those of the colonial state in the Saharan zone interact with both the long-term regional dynamics of the West-Saharan region, and the global context of an era of reconfigurations that sees former colonies integrate international organizations.